Doing Responsible Journalism: Journalists’ Perceptions of Ethiopian Orthodox Tewahedo Church Issues and Their Media Coverage - Kumlachew, Sileshie Semahagne (Journal of religion in Africa, 2025)
The Ethiopian Orthodox Tewahdo Church (EOTC) represents almost half of Ethiopia’s population and is the largest Orthodox group in the world, outside Europe. It has recently faced tensions. This survey of Ethiopian journalists’ (N = 221) understanding of the church’s situation and media coverage shows that while its societal role and relationship with ethnic and other religious groups is viewed positively by most, recent attacks have put it in a position of existential threat. The main reason for this is seen to be ethnic divisions instigated by religiously motivated, systemic government intervention. Instead of bringing this to light in accordance with professional journalistic standards, the mainstream media keep the issues in the dark. While self-censorship, editorial decisions and inaccessibility of religious leaders are factors in this neglect, state interference is seen as most prominent. Social media sites and EOTC-related media were found to cover the issues adequately.